World Elder Abuse Awareness Day : Well-Treatment in All Circumstances - Michaud, Julie (2021)

New Case-MCQ Program Provides Free Monthly Books to Young Readers - Ottier, Audrey; Vidal, Emily (2021)

[Dashboards - Quebec and RTS Territories] - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Mauricie-et-du-Centre-du-Québec - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS du Centre-de-la-Mauricie (0414) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de L'Energie (0403) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.